2017
DOI: 10.1186/s12943-017-0710-z
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-218 functions as a tumor suppressor in lung cancer by targeting IL-6/STAT3 and negatively correlates with poor prognosis

Abstract: BackgroundAberrant expression of microRNAs in different human cancer types has been widely reported. MiR-218 acts as a tumor suppressor in diverse human cancer types impacting regulation of multiple genes in oncogenic pathways. Here, we evaluated the expression and function of miR-218 in human lung cancer and ALDH positive lung cancer cells to understand the potential mechanisms responsible for disease pathology. Also, the association between its host genes and the target genes could be useful towards the bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 55 publications
4
88
0
Order By: Relevance
“…Subsequently, numerous studies demonstrated that miRNAs serve important roles in various carcinomas (22)(23)(24)(25)(26). In addition, Polioudakis et al (27) reported that miRNAs are located at 50% of all fragile regions or sites presenting copy number alterations in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, numerous studies demonstrated that miRNAs serve important roles in various carcinomas (22)(23)(24)(25)(26). In addition, Polioudakis et al (27) reported that miRNAs are located at 50% of all fragile regions or sites presenting copy number alterations in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Mir-218 negatively regulates the IL-6 receptor and JAK3 gene expression in lung CSCs. 338 In addition, some endogenous or exogenous genes inhibit JAK/STAT signaling in CSCs. Von Hippel-Lindau suppresses the tumorigenicity and self-renewal ability of glioma stem cells by inhibiting JAK2/STAT3.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%
“…miR-218 has been reported to be downregulated in several neoplasms and serves critical roles in tumorigenesis and metastasis. It exhibits low expression levels in numerous tumor tissues and is associated with patient prognosis (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%